2017
DOI: 10.1161/jaha.117.007564
|View full text |Cite
|
Sign up to set email alerts
|

Combining ECG Criteria for Left Ventricular Hypertrophy Improves Risk Prediction in Patients With Hypertension

Abstract: BackgroundPatients with hypertension with ECG left ventricular hypertrophy (LVH) have higher cardiovascular morbidity and mortality, but single ECG criteria may underestimate risk. Whether continued presence or new development of ECG LVH by 2 criteria can further concentrate risk during blood pressure lowering is unclear.Methods and ResultsIncident stroke, myocardial infarction, cardiovascular death, the composite of these outcomes, and all‐cause mortality were examined in relation to the presence of on‐treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 46 publications
1
29
0
1
Order By: Relevance
“…Many studies showed that ECG and ECHO LVH predict future adverse outcomes independently and complementarily . Moreover, some studies suggested that combination of Cornell product and Sokolow‐Lyon voltage increased sensitivity for the detection of LVH and coexistence of these two criteria further improved risk prediction for future cardiovascular events and all‐cause mortality . Previous studies usually adopted the most common ECG criteria, such as Cornell voltage/product or Sokolow‐Lyon voltage, whereas in present study we analyzed 18 single established criteria.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies showed that ECG and ECHO LVH predict future adverse outcomes independently and complementarily . Moreover, some studies suggested that combination of Cornell product and Sokolow‐Lyon voltage increased sensitivity for the detection of LVH and coexistence of these two criteria further improved risk prediction for future cardiovascular events and all‐cause mortality . Previous studies usually adopted the most common ECG criteria, such as Cornell voltage/product or Sokolow‐Lyon voltage, whereas in present study we analyzed 18 single established criteria.…”
Section: Discussionmentioning
confidence: 91%
“…; Okin et al. ). Thus, an increase in PP may be more predictive of cardiovascular risk than either SBP or DBP alone and that ideal antihypertensive therapy should be aimed at rigorous control of both SBP and DBP in order to maintain the PP within in a normal narrow range (Protogerou et al.…”
Section: Discussionmentioning
confidence: 96%
“…The Sokolow‐Lyon voltage criteria (S V1 + R V5/6 ) higher than 38 mm were used to identify LVH (Bacharova and Estes ; Okin et al. ) Echocardiography was done by cardiologists who were blinded to clinical data and ECG findings. Echocardiographic diagnosis of LVH was made based on the left ventricular mass index (LVMI), which was calculated from measurements of interventricular septum thickness, posterior wall thickness of left ventricle, and end‐diastolic left ventricular diameter (Lovic et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations